Pencegahan Hipotensi Pasca Anestesi Spinal pada Operasi Sectio Caesarea: Literature Review - Verra Rachma Indahsari; Khadafi Indrawan (CV. Jasa Sukses Abadi, 2026)
Spinal anesthesia is widely used for cesarean section, but it often causes hypotension due to sympathetic blockade, making vasopressor prophylaxis necessary. Ephedrine has long been the traditional choice, although several studies have linked it to a higher risk of neonatal acidosis. Phenylephrine is now more commonly recommended because of its effectiveness in maintaining blood pressure, while recent evidence suggests that norepinephrine may provide comparable hemodynamic stability with a lower incidence of maternal bradycardia. Literature searching was performed through PubMed, Google Scholar, and ScienceDirect using keywords related to ephedrine, phenylephrine, norepinephrine, hypotension, and spinal anesthesia for cesarean delivery. Articles discussing vasopressor use for the prevention or management of hypotension were reviewed and summarized narratively. The findings indicate that phenylephrine effectively maintains blood pressure but may cause bradycardia; norepinephrine at doses of 0.05 µg/kg/min offers hemodynamic stability similar to phenylephrine 0.625 µg/kg/min, with no significant differences in neonatal outcomes across several studies; and ephedrine remains useful, especially when maternal bradycardia occurs, although some research reports a higher risk of neonatal acidosis. Overall, the evidence is mixed and does not show clear superiority of one vasopressor over another. Both phenylephrine and norepinephrine can be used for prophylaxis of spinal-induced hypotension in cesarean section, each with its own advantages and limitations, while ephedrine remains relevant in specific situations. Further studies are needed to establish more definitive recommendations regarding the optimal vasopressor choice.